Assessing the potential of Therophilus javanus, a biological control candidate against the cowpea pod borer Maruca vitrata in West Africa - (:unkn) unknown (My University, 2018)
Maruca vitrata Fabricius (Lepidoptera: Crambidae) is one of the most important insect pests in West Africa causing severe damage to cowpea (Vigna unguiculata L. Walp. (Fabales: Fabaceae)). The pest alone can cause up to 80 % yield losses. Damage is done by caterpillars on flower buds, flowers and developing pods. To develop the biological control of M. vitrata in West Africa, a collaboration has been established between WorldVeg and IITA that resulted in the identification of one promising parasitoid species namely Therophilus javanus (Bhat & Gupta, 1977) (Hymenoptera: Braconidae). Because of a dearth of data concerning T. javanus biology, the present work was initiated to assess the suitability of T. javanus as a classical biological control agent against M. vitrata in West Africa.In order to help for decision making regarding the use of T. javanus as a biological control agent against the pod borer, my thesis focused on some biological parameters as egg production capacity in females, immature development, the impact of host stage on the adult life cycle and the ability of adult female to localize M. vitrata on infested host plant organs based on olfactory stimuli. I’ve also investigated the morphology, ultrastructural organization and the transcriptome of the venom gland in females, and designed a PCR method for detection of M. vitrata caterpillars parasitized by T. javanus.Our study has demonstrated that T. javanus is a synovigenic species that mature eggs gradually after emergence and that egg production in progeny is influenced by the size or instar of the caterpillar host at parasitism. T. javanus is a koinobiont endoparasitoid that has three larval instars: the first and the second instars are completed inside the host whereas the third instar is achieved outside the host. Development time and fecundity were influenced by the size or instar of the caterpillar at the moment of parasitism whereas mother longevity and progeny sex ratio
Keywords: African Research